2018
DOI: 10.6018/riite/2018/327881
|View full text |Cite
|
Sign up to set email alerts
|

Selección de categorías para el estudio de la evolución de la competencia digital docente del profesorado en Educación Superior

Abstract: La competencia digital docente (CDD) puede comprenderse como una competencia en evolución a lo largo de la trayectoria profesional del profesorado. Este es el tema de investigación de una tesis doctoral en curso, cuyo objetivo general es caracterizar la adquisición y el desarrollo en la práctica de la competencia digital de docentes universitarios para reconocer su influencia en su evolución profesional. En este artículo se presentan las categorías identificadas para el diseño de un guion de entrevista en prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Torelló & Pérez (2012) state that a good university teacher cannot be separated from the three main dimensions they develop (teaching, research and management), or from the areas where they put them into practice (social context, institutional context and classroom context). In this regard, as Pozos (2015) states, teachers must not only integrate the use of ICT into the curriculum but also promote research and participation in research projects with the support of ICT (Twalib, 2012) in order to promote the results of their good teaching practices (Padilla-Hernández & Vanesa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Torelló & Pérez (2012) state that a good university teacher cannot be separated from the three main dimensions they develop (teaching, research and management), or from the areas where they put them into practice (social context, institutional context and classroom context). In this regard, as Pozos (2015) states, teachers must not only integrate the use of ICT into the curriculum but also promote research and participation in research projects with the support of ICT (Twalib, 2012) in order to promote the results of their good teaching practices (Padilla-Hernández & Vanesa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Es decir, la pedagogía debe seguir ocupando un lugar principal a la hora de estructurar la modalidad híbrida de aprendizaje. Como señalan Lencastre y Coutinho (2015), aunque el aspecto digital sea el que más visiblemente despierta el cambio, es consensual que el uso de las tecnologías per se no supone necesariamente una mejora en la calidad de la educación (Padilla-Hernández, Gámiz Sánchez & Romero López, 2018).…”
Section: El Nuevo Papel De Profesoras Y Alumnas En Los Entornos B-lea...unclassified
“…In this context, ref. [ 27 ] recognize the need to deepen the understanding of the development of teachers’ digital competencies. The COVID-19 pandemic revealed that there are four teacher kinds: (a) the enthusiast, (b) the skeptic, (c) the pessimist, and (d) the affirmative [ 1 ].…”
Section: Introductionmentioning
confidence: 99%